BUDAYA ORGANISASI DAN MOTIVASI KERJA DAN KAITANNYA DENGAN KINERJA GURU - Arwadi Arwadi; Ruhita Ruhita (Edum Journal, 2019)
This study aims to explore more about the conditions of organizational culture and work motivation of teachers and their influence on the performance of State Junior High School (SMP) teachers in Sector 5 in Indramayu Regency. This type of research is descriptive analytical. The population in this study were all state junior high school teachers in Sector 5 in Indramayu District. The number of teachers in the Public Middle School in Sector 5 of Indramayu Regency was 420 people, namely 81 junior high school teachers in Sector 5 in Sector 5 in Indramayu Regency. Data analysis in this study used descriptive data analysis and multiple regression. The results of the study inform that: (1) there is a positive and significant influence between organizational culture on teacher performance in the Public Middle School in Sector 5 of Indramayu Regency, and the amount of contribution is 7.4%. (2) there is a positive and significant influence between teacher work motivation on teacher performance in the Public Middle School in Sector 5 of Indramayu Regency, and (2) the amount of contribution is 19%. (3) there is a positive and significant influence between organizational culture and teacher work motivation together on the performance of teachers in the Public Middle School in Sector 5 of Indramayu Regency, and (2) the contribution is 22.9%, while the rest is influenced by other factors that do not discussed in this study.